Hubungan praktik pemberian makanan pendamping ASI pada anak dengan kejadian stunting - dea afriyani (HEALTH CARE : JURNAL KESEHATAN, 2022)
Abstract The correlation beetwen the practice of complementary feeding for children with incidence of stunting. Aim: Complementary feeding is aimed to provide children with nutritious foods and drinks other than breast milk to help them grow well and to prevent them from nutrition problems. Inappropriate complementary feeding will lead to malnutrition, which is a major factor of stunting among children. The purpose of this study was to determine the correlation between complementary feeding practice and stunting among children. Method: This study applied cross sectional approach. The samples for this study were 150 mothers with children aged 6-24 months, who were selected using purposive sampling method. The data were collected using questionnaire regarding complementary feeding practice, completed with the data of children’s body length provided by Puskesmas (Community Health Centre) Rejosari. Result: The results of the study showed that there was a correlation between the age of the complementary feeding (p=0,006) with stunting, while other factors of frequency (p=0,815), texture (p=0,681), amount (p=0,695), and nutrition (p=0,374) showed no correlations. Conclusion: It is suggested that complementary feeding for breastfed children should consider the age of feeding in the order to reduce the risk of stunting. Keywords: Complementary Feeding, age, frequency, nutrition, texture, amount, stunting, children